2017
DOI: 10.1111/1471-0528.15007
|View full text |Cite
|
Sign up to set email alerts
|

Hospital variation in cost of childbirth and contributing factors: a cross‐sectional study

Abstract: Hospitals vary in cost of childbirth. Institutional characteristics significantly contribute to the variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…According to the administrative region of the country, OOP was highest for the Dhaka division, as Dhaka is the capital of Bangladesh and the living cost was higher than those of other regions in the country. The study showed that the richest wealth quintile spent significantly more than poorest quintile, although higher cost does not always guarantee the better birth outcome . However, it was well reported that the wealthiest households always used more maternal care services than those in the poorest households, in the Bangladeshi context .…”
Section: Discussionmentioning
confidence: 96%
“…According to the administrative region of the country, OOP was highest for the Dhaka division, as Dhaka is the capital of Bangladesh and the living cost was higher than those of other regions in the country. The study showed that the richest wealth quintile spent significantly more than poorest quintile, although higher cost does not always guarantee the better birth outcome . However, it was well reported that the wealthiest households always used more maternal care services than those in the poorest households, in the Bangladeshi context .…”
Section: Discussionmentioning
confidence: 96%
“…25 Examples included maternal age, parity, fetal presentation, gestational age, hypertensive disorders of pregnancy, adequacy of prenatal care, and whether mother was transferred-in. 25 Examples included maternal age, parity, fetal presentation, gestational age, hypertensive disorders of pregnancy, adequacy of prenatal care, and whether mother was transferred-in.…”
Section: Patient Risk Factorsmentioning
confidence: 99%
“…25 Examples included maternal age, parity, fetal presentation, gestational age, hypertensive disorders of pregnancy, adequacy of prenatal care, and whether mother was transferred-in. 25 They were measured using birth certificate data elements, as well as diagnosis codes and admission source documented on hospital discharge records.…”
Section: Patient Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, prior studies have reported wide variability in the provision of maternal care, leading to uctuations in overall childbirth costs (3)(4)(5). This phenomenon has generated substantial interest, with researchers particularly focusing on facility-related characteristics and their impact on cost variability (6)(7)(8). However, the available literature offers less information about the factors driving cost variation within hospitals.…”
Section: Introductionmentioning
confidence: 99%